The origins of Christian anti-internationalism: conservative evangelicals and the League of Nations - Ruotsila, Markku (Religion and politics series, 2008)
The social gospel and modern internationalism -- Dispensationalists : prefiguring the Latter days -- Calvinists : contesting the public means of grace -- Lutherans : the two kingdoms and the Antichrist -- Methodists and Episcopalians : a few dissenting voices -- Religion and the League fight in the Senate -- Religion and the League for the preservation of American independence -- The persistence of Christian anti-internationalism